Hydrological Load and a Review of Hydro-Mechanical Behaviour of the Bengal Aquifer System (The Dhaka University Journal of Earth and Environmental Sciences, 2025)
In traditional hydrogeologic interpretation, the contribution of loading impacts and the associated hydro-mechanical aquifer behaviour are usually ignored. In certain circumstances however, they may have significant implications for water budget studies, groundwater monitoring and therefore resource assessment. Hydrological loading influences on groundwater in the Bengal Aquifer System (BAS) have recently been recognized at individual sites in Bangladesh. This review accumulates evidences to extend knowledge of BAS hydro-mechanical behaviour, to establish the significance of these coupled processes which under-pin groundwater variations in this environment. From the review, it may be realized that aquifer hydro-mechanical behaviour needs to be more fully considered in the BAS to interpret groundwater level data and groundwater storage changes. Therefore, further investigation of the scale and implications of hydro-mechanical coupling in specific hydrogeological settings and in the context of specific loading sources are needed, so that the effects may be properly recognized.The Dhaka University Journal of Earth and Environmental Sciences, Vol. 13(2), 2024, P 17-30